2003
DOI: 10.1093/hmg/ddg323
|View full text |Cite
|
Sign up to set email alerts
|

Testing the position-effect variegation hypothesis for facioscapulohumeral muscular dystrophy by analysis of histone modification and gene expression in subtelomeric 4q

Abstract: Facioscapulohumeral muscular dystrophy (FSHD) is a unique dominant disorder involving shortening of an array of tandem 3.3 kb repeats. This copy-number polymorphic repeat, D4Z4, is present in arrays at both 4q35 and 10q26, but only 4q35 arrays with one to 10 copies of the repeat are linked to FSHD. The most popular model for how the 4q35 array-shortening causes FSHD is that it results in a loss of postulated D4Z4 heterochromatinization, which spreads proximally, leading to overexpression of FSHD genes in cis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
126
1
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(138 citation statements)
references
References 69 publications
9
126
1
2
Order By: Relevance
“…This argues against a cis spreading effect from D4Z4 in proximal direction. Also analysis of histone modifications in 4qter argues against this disease model for FSHD [22] . We propose that the recently identified CTCF binding site at the proximal end of the D4Z4 repeat (G. Filippova, personal communication) may prevent spreading of hypomethylation in a proximal direction.…”
Section: D4z4 Hypomethylation Is Restricted To the D4z4 Repeat Arraymentioning
confidence: 99%
See 2 more Smart Citations
“…This argues against a cis spreading effect from D4Z4 in proximal direction. Also analysis of histone modifications in 4qter argues against this disease model for FSHD [22] . We propose that the recently identified CTCF binding site at the proximal end of the D4Z4 repeat (G. Filippova, personal communication) may prevent spreading of hypomethylation in a proximal direction.…”
Section: D4z4 Hypomethylation Is Restricted To the D4z4 Repeat Arraymentioning
confidence: 99%
“…The absence of FRG2 on the disease alleles in some FSHD patients with a proximal deletion makes this gene a less attractive candidate gene [39] . However, transcriptional deregulation of these candidate genes in patients with FSHD is still under debate, as several studies showed contradictory results [22,[40][41][42][43] . Based on our data showing that hypomethylation is restricted to the D4Z4 repeat and not spreading in a proximal direction in addition to previous data showing no change in the chromatin structure of proximal sequences in FSHD [22] , we do not support a cisspreading mechanism emanating from D4Z4 in FSHD.…”
Section: D4z4 Hypomethylation Is Restricted To the D4z4 Repeat Arraymentioning
confidence: 99%
See 1 more Smart Citation
“…[42][43][44][45] This proximal anchoring may provide a relatively high mobility of the 4q end, which has a large diffusion volume, change by the length of D4Z4 array (Fig. 3).…”
mentioning
confidence: 99%
“…Changes in levels and patterns of DNA methylation also have an important role in oncogenesis [3] . In healthy individuals, the chromatin structure of the D4Z4 region on chromosome 4q35 is highly methylated, and resembles that of heterochromatin or transcriptional inactive euchromatin [4][5][6] . A currently favored hypothesis is that the marked hypomethylation of the D4Z4 region in FSHD might cause a change in the chromatin structure, and consequently a transcriptional deregulation of one or more genes in the vicinity, or at a distance of the D4Z4 repeat array [1,6] .…”
Section: Introductionmentioning
confidence: 99%